Diseño arquitectónico de mercado comunal con arquitectura bioclimática en la Isla puná - Arévalo Bustamante, Josué Alexander (2025)
This thesis project aims to design a community market with bioclimatic criteria for the community of Puná Island, located in the province of Guayas. This proposal addresses the urgent need for commercial spaces suitable for users, promoting local economic development and improving the working conditions of the island's merchants and producers. The market is conceived not only as a place for the exchange of goods, but also as a cultural and social center that reinforces local identity. The methodology is based on a territorial and social assessment of the community, considering environmental, climatic, and urban aspects to ensure a functional, sustainable, and contextualized design. Bioclimatic architectural principles were adopted, using materials appropriate for the island's environment and respecting the climatic conditions of the area. The design includes public, semi-public, and private spaces, strategically distributed to optimize circulation, natural lighting, and cross ventilation..............